Twelve exonic variants in the SLC12A1 and CLCNKB genes alter RNA splicing in a minigene assay - Xin, Qing; Liu, Qihua; Liu, Zhiying; Shi, Xiaomeng; Liu, Xuyan; Zhang, Ruixiao; Hong, Yefeng; Zhao, Xiangzhong; Shao, Leping (Frontiers in Genetics, 2022)
Abstract Background: Bartter syndrome (BS) is a rare renal tubular disease caused by gene variants in SLC12A1, KCNJ1, CLCNKA, CLCNKB, BSND or MAGED2 genes. There is growing evidence that many exonic mutations can affect the pre-mRNA normal splicing and induce exon skipping by altering various splicing regulatory signals. Therefore, the aim of this study was to gain new insights into the consequences of exonic mutations associated with BS on pre-mRNA splicing. Methods: We analyzed all the missense, nonsense and synonymous variants described in six pathogenic genes by bioinformatics programs and identified candidate mutations that may promote exon skipping through a minigene system. Results: Results of the study showed that 12 of 14 candidate variants distributed in SLC12A1(c.728G>A, C.735C>G, c.904C>T, c.905G>A, c.1304C>T, c.1493C>T, c.2221A>T) and CLCNKB (c.226C>T, c.228A>C, c.229G>A, c.229G>C, c.1979C>A) were identified to induce splicing alterations. These variants may not only disrupt exonic splicing enhancers (ESEs) but also generate new exonic splicing silencers (ESSs), or disturb the classic splicing sites. Conclusion: To our knowledge, this is a comprehensive study regarding alterations in pre-mRNA of exonic variants in BS pathogenic genes. Our results reinforce the necessity of assessing the consequences of exonic variants at the mRNA level.